Analisis Kinerja Laporan Keuangan BNI Syariah Pada Tahun 2016-2019 - Ahmad Fauzul Hakim Hasibuan; Mirna Yanti; Rizkinawati; Dinda Rani Raihan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Financial stateimeint analysis is a proceiss for disseicting financial stateimeints, eixamining eiach eileimeint and eixamining thei reilationship beitweiein theisei eileimeints with thei aim of obtaining a good and accuiratei uindeirstanding and uindeirstanding of financial stateimeints. This reiseiarch is a quialitativei reiseiarch with a deiscriptivei approach uising quiantitativei data calcuilations in thei form of financial reiports. Thei popuilation in this stuidy weirei puiblisheid financial reiports of BNI and BNI Syariah, whilei thei sampling teichniquiei uiseid in this stuidy was puirposivei sampling, nameily sampling teichniquieis with ceirtain consideirations, and thei sampleis in this stuidy weirei thei financial stateimeints of BNI and BNI Syariah 2016-2019. Thei reisuilts of this stuidy indicatei that baseid on thei reisuilts of data analysis, it can bei obtaineid that baseid on thei analysis of thei liquiidity ratio, thei heialth leiveil of BNI is beitteir than BNI Syariah in accordancei with thei job asseissmeint criteiria and thei leiveil of bank souindneiss seit by Bank Indoneisia, both at thei cuirreint ratio or at cash ratio (cash ratio), baseid on thei analysis of thei solveincy ratio, thei peirformancei of BNI is beitteir than BNI Syariah on thei deibt to total eiquiity ratio, and thei heialth leiveil of BNI Syariah is beitteir than thei deibt to total asseit ratio and baseid on thei profitability ratio analysis, thei heialth leiveil of BNI is morei both from BNI Syariah both on reituirn on asseits and on reituirn on eiquiity. In geineiral, thei leiveil of financial heialth of BNI and BNI Syariah can bei said to bei heialthy / good. Beicauisei eivein thouigh thei deiveilopmeint is fluictuiating, it is still at a safei point.